EVALUASI PROGRAM PENGGEMUKAN SAPI DI KECAMATAN LINGE KABUPATEN ACEH TENGAH - Nanda Zunafriesma; Hasan Basri; Achmad Surya (Dialogue : Jurnal Ilmu Administrasi Publik, 2022)
Through the Qanun of Central Aceh Regency Number 6 of 2013, the Ketapang Nusantara Integrated City Area (KTM) was established in Linge District, Central Aceh Regency. Beef cattle fattening farm program in 2013. This study aims to evaluate the cattle fattening program in Ketapang Nusantara. This type of research is descriptive qualitative. The informants of this research include the Head of the Dians Animal Husbandry, Central Aceh Regency, Cattle Cattle Group in Linge District, Central Aceh Regency, the community and related stakeholders. The results showed that the cattle fattening program could be said to be ineffective as a whole because the fulfillment of meat needs was still in the district of Central Aceh, while the objective of the program was based on regulations, namely meeting the needs of beef in the Special Province of Aceh. Besides that, some of the obstacles faced are natural factors, not being able to provide pasture to meet the quantity of animal feed, because some areas have land contours that are dominant with rocks. Behavior factors of human resources, lack of innovation and creativity of breeders in managing their farms. As well as the Organizational Commitment Factor, the weak commitment of the Department of Agriculture in coordinating and collaborating with related parties. The recommendations formulated include the need for partnerships with academics, improved coordination with agencies related to the cattle fattening program, and there needs to be a search for more supportive livestock locations.